2014
DOI: 10.1016/j.bbmt.2014.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Donor Engraftment in Recipients of Double-Unit Cord Blood Transplantation Is Possible Despite Donor-Specific Human Leukoctye Antigen Antibodies

Abstract: The impact of human leukocyte antigen (HLA) donor-specific antibodies (DSA) upon cord blood (CB) engraftment is controversial. We evaluated the influence of pre-existing HLA-antibodies (HLA-Abs) on engraftment in 82 double-unit CB recipients (median age 48 years) transplanted for hematologic malignancies. Of 28 patients (34%) with HLA-Abs, 12 had DSA (median MFI 5,255, range 1,057–9,453). DSA patients had acute leukemia (n = 11) or myelodysplasia (n = 1) and all received either high-dose or reduced intensity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Although several studies have shown a strong association of preformed donor-specific HLA antibodies (DSA) with primary graft failure after unrelated donor transplantation 32,33 and related haploidentical donor transplantation, 94,95 the data in the setting of CB transplants are mixed, with some reporting an adverse effect and others none. [96][97][98][99] Thus, for patients with anti-HLA antibodies and a mismatched allograft, careful antibody specificity analysis and/or testing of the patient's serum for reactivity with cells from potential donors (ie, cross-matching) should be done prior to transplantation Cryopreserved cell dose|| ¶# Single-unit CBT: minimum dose/kg TNC $2.5 3 10 7 /kg and CD34 1 cells $1.5 3 10 5 /kg (some centers recommend higher CD34 1 dose as minimum) Double-unit CBT: minimum dose/kg per unit TNC 1.5 3 10 7 /kg for each unit and CD34 1 cells $1.0 3 10 5 /kg for each unit (some centers recommend higher CD34 1 doses for each unit as minimum)…”
Section: Consideration Of Non-hla Factorsmentioning
confidence: 99%
“…Although several studies have shown a strong association of preformed donor-specific HLA antibodies (DSA) with primary graft failure after unrelated donor transplantation 32,33 and related haploidentical donor transplantation, 94,95 the data in the setting of CB transplants are mixed, with some reporting an adverse effect and others none. [96][97][98][99] Thus, for patients with anti-HLA antibodies and a mismatched allograft, careful antibody specificity analysis and/or testing of the patient's serum for reactivity with cells from potential donors (ie, cross-matching) should be done prior to transplantation Cryopreserved cell dose|| ¶# Single-unit CBT: minimum dose/kg TNC $2.5 3 10 7 /kg and CD34 1 cells $1.5 3 10 5 /kg (some centers recommend higher CD34 1 dose as minimum) Double-unit CBT: minimum dose/kg per unit TNC 1.5 3 10 7 /kg for each unit and CD34 1 cells $1.0 3 10 5 /kg for each unit (some centers recommend higher CD34 1 doses for each unit as minimum)…”
Section: Consideration Of Non-hla Factorsmentioning
confidence: 99%
“…The issues with red cell content are discussed in the Thaw and Infusion section. The relative importance of avoidance of units against which the patient may have donor specific anti-HLA antibodies (DSA) is controversial with conflicting studies showing that they may 53,54 or may not 55,56 be important. Further investigation is required to resolve this question taking into account factors such as the patient’s prior therapy (that could influence risk for T-cell mediated rejection), the intensity of the conditioning regimen and use of ATG, the type of graft, and the number of antibodies, their titer and complement fixation.…”
Section: Graft Selectionmentioning
confidence: 99%
“…Although there are conflicting data regarding the importance of HLA antibodies in the setting of CBT (Brunstein et al , ; Dahi et al , ), the presence of donor‐specific anti‐HLA antibodies (DSA) has been shown to adversely affect neutrophil and platelet engraftment in both ablative and RIC settings, using single or double unit CB grafts (Cutler et al , ; Ruggeri et al , ) and may also be associated with a higher TRM (Ruggeri et al , ) and inferior survival (Cutler et al , ). In light of these observations, all recipients should be screened for anti‐HLA antibodies prior to transplant and CBUs for which the recipient has high levels of DSA should be avoided.…”
Section: Selection Of Umbilical Cord Blood Unitsmentioning
confidence: 99%
“…Although there are conflicting data regarding the importance of HLA antibodies in the setting of CBT (Brunstein et al, 2011;Dahi et al, 2014), the presence of donor-specific anti-HLA antibodies (DSA) has been shown to adversely affect neutrophil and platelet engraftment in both ablative and RIC settings, using single or double unit CB grafts (Cutler et al, 2011;Ruggeri et al, 2013) and may also be associated with a higher TRM (Ruggeri et al, 2013)…”
Section: Anti-hla Antibodiesmentioning
confidence: 99%